2015
DOI: 10.5265/jcogpsy.12.101
|View full text |Cite
|
Sign up to set email alerts
|

Developing group-format reading span tests of English and Japanese for high-school students and investigating the relationship between working memory and English proficiency

Abstract: e present study develops group-format reading span tests RSTs of Japanese and English for Japanese high-school students and investigates whether it is feasible to administer the tests to groups within reasonably short periods. Reliability coe cients for the newly-developed RSTs were high; for Japanese, α .864 and for English, α .875. Moreover, test scores were found to be normally distributed. ese ndings indicate that the RSTs are e ective for group administration. Further analyses of correlation di erences be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Various theoretical orientations have been discussed regarding the connection between the L1 and the L2, including the interdependence hypothesis, the threshold hypothesis, and the dual-language system. In addition, many studies have found that the working memory capacity in the L1 and L2 are strongly correlated (e.g., Osaka & Osaka, 1992;Osaka, Osaka, & Groner, 1993;Shibasaki, Tokimoto, Ono, & Inoue, 2015). As a result of these findings, L1 literacy has been included in the L2 reading model.…”
Section: Relationship Between L1 Literacy and L2 Reading Abilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Various theoretical orientations have been discussed regarding the connection between the L1 and the L2, including the interdependence hypothesis, the threshold hypothesis, and the dual-language system. In addition, many studies have found that the working memory capacity in the L1 and L2 are strongly correlated (e.g., Osaka & Osaka, 1992;Osaka, Osaka, & Groner, 1993;Shibasaki, Tokimoto, Ono, & Inoue, 2015). As a result of these findings, L1 literacy has been included in the L2 reading model.…”
Section: Relationship Between L1 Literacy and L2 Reading Abilitymentioning
confidence: 99%
“…The English RST (Shibasaki et al, 2015) was used for the study. This is the only test of its kind developed specifically for Japanese high school students, and it showed a relatively higher reliability (Cronbach's alpha = .875).…”
Section: English Reading Span Test (Rst)mentioning
confidence: 99%